Rhabdomyosarcoma Presenting as Bilateral Cervical Lymphadenopathy in an Adult with Aberrant Expression of Cytokeratin and Synaptophysin: A Potentially Serious Diagnostic Pitfall - Sukumaran, Renu; Mathews, Anitha; Nayak, Nileena; Kattoor, Jayasree (Annals of Pathology and Laboratory Medicine, 2021)
Rhabdomyosarcoma (RMS) is the most common soft tissue malignancy in children and adolescents. Its occurrence in patients more than 18 years of age is rare. Subtypes of rhabdomyosarcoma include embryonal RMS, alveolar RMS, pleomorphic RMS and spindle/sclerosing RMS. Herein, we report the case of a 42-year-old female patient who presented with bilateral cervical lymphadenopathy of two-month duration. Clinical and radiological examination showed no other significant lesions. Fine needle aspiration cytology and biopsy of lymph node showed diffusely arranged atypical round cells. The clinical findings and morphology pointed to a hematolymphoid malignancy. On immunohistochemical examination, the atypical cells were negative for CD45, CD20, CD3, PAX5 and CD30. The cells showed patchy moderate positivity for cytokeratin, focal weak positivity for synaptophysin and were negative for chromogranin, CD56 and TTF1. On further evaluation, patchy strong positivity for desmin, myogenin and myo D1 were noted. Correlating the morphology and immunoprofile, diagnosis of rhabdomyosarcoma was given. Multiple peripheral lymph node enlargement without an obvious primary lesion is a rare presentation of alveolar RMS, with only a few cases reported in literature. Unusual clinical presentation complicated with aberrant expression of epithelial markers may make the diagnosis of alveolar RMS difficult. This case demonstrates the importance of considering extensive differential diagnosis for neck masses with poorly differentiated morphology.